Investigation of human thermal comfort and energy efficiency in tropical buildings - Nurjihan Mohammed Noor. (2011)
Thermal comfort is very important to many work-related factors. It can affect the concentration levels of the workers, and in turn affect their performance and productivity. Also, thermal discomfort is known to be the cause of sick building syndrome symptoms. High temperature and high relative humidity reduces thermal comfort and indoor air quality.In view of thermal comfort as a whole, human thermal influences and the human thermal comfort needs to be considered and compared with other hot and humid countries such as Japan, India and China. Sustainable thermal comfort and natural ventilation were also looked into.